Evaluation of the Samisade (Satu Miliar Satu Desa) Program in Bogor Regency - Michel, Diana; Mutiarin, Dyah; binti Abdul Manaf, Halimah (Universitas Pendidikan Ganesha, 2024)
This study aims to evaluate the Satu Miliar Satu Desa (Samisade) program. The Samisade initiative in Bogor Regency has been funding village infrastructure since 2021 with the goal of fostering regional development in rural areas. This research focuses on the Samisade program, which aims to improve rural economies, reduce poverty, and promote local development. Data was collected through online news and in-depth observations from community members, village heads, sub-district heads, agencies, and the regent of Bogor Regency. The study uses descriptive-qualitative methods and Nvivo 12 Plus tools to analyze the data, ensuring the program's effectiveness and meeting community expectations. The research provides a comprehensive understanding of the program's impact on rural development. According to the study, the Samisade program in Bogor Regency has greatly aided village officials in developing infrastructure, promoting health, education, and growth-oriented programs, and controlling and carrying out accountability. The initiative was funded by an IDR 7.6 trillion budget increase of 10% for 2021, which allowed the program's debut in 2020. Despite obstacles, the Samisade Program in Bogor Regency has been successfully carried out, with its goals, objectives, and techniques being recognized. It has contributed to ongoing infrastructural improvement and economic growth.